THE EFFECTIVENESS OF SCLEROTHERAPY IN THE TREATMENT OF HYPERTROPHIC GINGIVITIS - Aliyeva, G.H. (World of Medicine and Biology, 2024)
The etiology, pathogenesis and treatment of gingivitis are one of the pressing and unresolved problems of modern dentistry. In this regard, among periodontal diseases, hypertrophic gingivitis is of particular importance. It is known that hypertrophic gingivitis is characterized by the complexity of etiopathogenesis, chronic course and the presence of a false gingival pocket compared to catarrhal and ulcerative-necrotizing gingivitis. At the same time, the treatment of this pathology requires a wider range of treatment compared to others, since in many cases the results of the treatment used are not effective and long-lasting. Taking this into account, we performed sclerotherapy with a dental drug based on lauromacrogol-400 in the treatment of chronic fibrous-hypertrophic gingivitis. As a result of the studies, it was established that as a result of using the drug for the purpose of sclerotherapy, the main symptoms of hypertrophic gingivitis were eliminated in a short time, and the treatment was long-term. This is confirmed by the results of observations carried out 6 and 12 months after the end of treatment, respectively.